Development of laundry mobile application with flutter and dart - Chuah, Jin Hao (2022)

(untitled)
Currently, the spreading of coronavirus had forced the government to implement the Movement Control Order which restricts the outdoor activity of the public. During this period, many businesses sector having a hard time to survive and even some of them had already closed up permanently due to a short budget to continue the business especially the laundry business sector. Therefore, this project is being introduced to aid in the digitalization of the laundry business sector by developing an android dedicated mobile laundry application for them. There are lots of existing mobile laundry applications but most of them are only available in foreign countries. Hence, this project will provide a good insight into how to build a laundry application that is compatible with the local laundry business activity